Correction to: miRNA-23b as a biomarker of culture-positive neonatal sepsis - Ahlam Fatmi; Sid Ahmed Rebiahi; Nafissa Chabni; Hanane Zerrouki; Hafsa Azzaoui; Yamina Elhabiri; Souheila Benmansour; José Santiago Ibáñez-Cabellos; Mohammed Chems-Eddine Smahi; Mourad Aribi; José Luis García-Giménez; Federico V. Pallardó (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.